Embedding knowledge into BIM: A case study of extending BIM with firefighting plans. (15th May 2022) - Kong, Linlin; Yang, Qiliang; Zhou, Qizhen; Xing, Jianchun; Sun, Xiaobo; Zou, Rongwei
Abstract: Building information modelling (BIM) has revolutionized production and operations management in the construction industry. Currently, however, the BIM environment can integrate only basic static information. Expert knowledge information to guide the building activity process is lacking. Consequently, with the increasing complexity of building services, BIM has difficulty adapting to the needs of rapid collaboration in the building operation process. To solve this problem, first, we present the basic knowle-dge-embedded model. The model provides services for knowledge generation and knowledge embedding. Moreover, taking BIM-based fire emergency management as an example, the formal modelling and credibility verification of knowledge are adopted to standardize the knowledge generated from experts to reduce future input errors and interpretation. Second, to provide the capability of process knowledge representation in BIM, we embedded the knowledge of the fire emergency management process into BIM by extending the Industry Foundation Classes (IFC) standard and providing a BIM knowledge extraction algorithm using the IFC standard, thereby extracting the control strategy from BIM to achieve the reasoning of knowledge. Finally, we prototyped BIM-Fire in a real building scenario and validated the effectiveness of the method. The automatic control of knowledge-driven BIM-based activities is realized. Highlights: A method that combines the static model of BIM with knowledge information from experts is proposed. The knowledge information is integrated into BIM by extending the IFC standard. An automatic method that transforms BIM knowledge into a control strategy is established. A prototype system platform is built and applied to a real project.